Kedewasaan digital: Sebuah konstruksi formasi spiritual dalam meminimalisir sikap adiktif internet pada remaja Kristen - Hasugian, Johanes Waldes; Simamora, May Rauli (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
This study reveals the impact of excessive internet use on Christian vocational high school students and then offers digital maturity through spiritual formation to minimize their addictive attitude. The research approach was quantitative-qualitative (mixed), using a survey method among 169 Christian students at one of the SMKs in North Tapanuli Regency, North Sumatra, and using some research literature to offer the concept of digital maturity. The results showed that there were negative impacts such as lack of sleep, sore/blurred eyes, weight gain/loss; cognitive distortion, foul or abusive language, decreased achievement; conflict with/scolded by parents, lack of interaction with parents, lying to parents, lack of interaction with peers, anxiety, anger, depression, aggressive behavior; procrastination in worship. This study also highlights the importance of spirituality formation in helping SMK students overcome the negative impact of excessive internet use. Wise and ethical use of the internet per Christian values can help students achieve life balance, in addition to the role of parents in monitoring internet use. This study recommends digital maturity as the digital spirituality of vocational students using the internet. Abstrak Penelitian ini mengungkapkan dampak penggunaan internet yang berlebihan pada siswa Sekolah Menengah Kejuruan (SMK) yang beragama Kristen, yang kemudian menawarkan kedewasaan digital melalui formasi spiritual demi meminimalisir sikap adiktif mereka. Pendekatan penelitian adalah kuantitatif-kualitatif (mixed), menggunakan metode survei pada 169 siswa beragama Kristen di salah satu SMK, di Kabupaten Tapanuli Utara, Sumatera Utara, selain menggunakan beberapa literatur hasil riset untuk menawarkan konsep kedewasaan digital. Hasil penelitian menunjukkan adanya dampak negatif yang ditemukan akibat penggunaan internet secara adiktif. Penelitian ini juga menyoroti peran penting formasi spiritualitas dalam membantu siswa SMK mengatasi dampak negatif dari penggunaan internet yang berlebihan. Penggunaan internet yang bijak dan etis sesuai dengan nilai-nilai kristiani dapat membantu siswa mencapai keseimbangan hidup, selain peran orang tua dalam memantau penggunaan internet. Penelitian ini merekomendasikan kedewasaan digital sebagai spiritualitas digital para siswa SMK dalam penggunaan internet.